Inhibition Effect of Phenyllactic Acid on Foodborne Vibrio vulnificus Biofilms - Yanfang ZHANG; Shuilin LIU; Mengjia GUO; Mengmin LÜ; Xinran LÜ; Fengling BAI; Jianrong LI; Fangchao CUI; Xiqian TAN; Hao DONG (Shipin gongye ke-ji)
In this study, the inhibitory effect of phenyllactic acid (PLA) on Vibrio vulnificus biofilm formation at sub-inhibitory concentration was studied. Firstly, the biofilm model of V. vulnificus was established. Then the inhibitory effect of PLA on the formation mass and metabolic activity of V. vulnificus biofilm was analyzed using crystal violet staining method and XTT reduction assay. Using extracellular polysaccharides, extracellular proteins, and extracellular DNA as indicators, the effect of PLA on the extracellular polymers of V. vulnificus was evaluated. The effect of PLA on the structure of V. vulnificus biofilm was investigated by optical microscopy and laser confocal microscopy. The results showed that the aggregation, maturation and shedding periods of V. vulnificus biofilm were at 16~32, 32~56, and 56~72 h, respectively. PLA at 0.5 MIC inhibited the biofilm of V. vulnificus in the maturation stage better, and the inhibition rates of biofilm formation mass, metabolic activity, extracellular polysaccharides, extracellular proteins, and extracellular DNA were 51.04%, 33.62%, 61.97%, 32.70%, and 52.25%, respectively. Additionally, PLA disrupted the density and integrity of V. vulnificus biofilms, resulting in a dispersed distribution of bacteria. Therefore, PLA inhibited the biofilm formation of V. vulnificus by reducing the formation of extracellular polymers. This study provides a theoretical basis for the control of V. vulnificus biofilm in aquatic products.